2020
DOI: 10.1111/mmi.14499
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory circuits controlling Spx levels in Streptococcus mutans

Abstract: An occasional inhabitant of the dental plaque, Streptococcus mutans is regarded as the major bacterial agent responsible for the initiation and progression of dental caries (Nakano et al., 2010a; Bowen et al., 2018). Upon oral colonization, S. mutans metabolizes dietary carbohydrates to produce an acidic biofilm matrix that challenges the survival of less aciduric bacteria, which includes members of the mitis streptococci group such as Streptococcus sanguinis and Streptococcus gordonii (Lemos and Burne, 2008).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…Consistent with these findings are reports implicating the S. mutans PerR regulator as a repressor of dpr and sod transcription(27). In addition, a recent report describes corepression of the S. mutans spxA1 gene by the PerR and SloR metalloregulators(33). The spxA1 gene product has been previously described as a positive regulator of oxidative stress tolerance in S. mutans(33)(34)(35).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Consistent with these findings are reports implicating the S. mutans PerR regulator as a repressor of dpr and sod transcription(27). In addition, a recent report describes corepression of the S. mutans spxA1 gene by the PerR and SloR metalloregulators(33). The spxA1 gene product has been previously described as a positive regulator of oxidative stress tolerance in S. mutans(33)(34)(35).…”
supporting
confidence: 58%
“…In addition, a recent report describes corepression of the S. mutans spxA1 gene by the PerR and SloR metalloregulators(33). The spxA1 gene product has been previously described as a positive regulator of oxidative stress tolerance in S. mutans(33)(34)(35). Clearly, further investigation is warranted to decipher the complexities of antioxidant gene regulation involving SpxA1.In summary, we propose that PerR is a prevalent redox sensing metalloregulator in S. mutans and that H2O2 is the possible signaling molecule that activates PerR and promotes S. mutans stress adaptation.…”
mentioning
confidence: 99%
“…Our manual searches identified four additional genes (mntH, spxA1, sodA and smu995) with putative PerR-binding boxes albeit, these additional motifs contained four mismatches from the consensus, with the exception of sodA that contained only one mismatch (Table 1). Of note, we recently showed that spxA1 is co-repressed by PerR and SloR in a redundant manner as only the simultaneous inactivation of perR and sloR increased spxA1 transcription (36). Overall, a trend was observed showing that expression levels of most of the genes tested were elevated in UA-perR and UA∆perR as compared to UA159, the iron transport systems feoAB and smu995-998 were the notable exceptions (Fig.…”
Section: Exploration Of the Regulatory Reach Ofmentioning
confidence: 81%
“…In addition, a recent report describes corepression of the S. mutans spxA1 gene by the PerR and SloR metalloregulators (33). The spxA1 gene product has been previously described as a positive regulator of oxidative stress tolerance in S. mutans (33)(34)(35). Clearly, further investigation is warranted to decipher the complexities of antioxidant gene regulation involving SpxA1.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent PerR binding to Fur-and PerR-like consensus sequences is then enabled (27). In addition, a recent report describes corepression of the S. mutans spxA1 gene by the PerR and SloR metalloregulators (33). The spxA1 gene product has been previously described as a positive regulator of oxidative stress tolerance in S. mutans (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%